Penguatan Branding Batik Khas Kota Cilegon Melalui Pelatihan Digital Marketing - Sonda, Atia; Wicaksono, Agung Satrio; Sholihin, Miftahus; Mahuda, Isnaini; Arina, Faula; Rahma, Midia; Alisya, Regina Dwirahma; Ichsan, Andhika Muhamad; Faiz, Syukron (Universitas Muhammadiyah Mataram, 2026)
Abstract: Rinara Batik, a micro, small, and medium enterprise (MSME), is one of the producers of traditional batik from Cilegon City. To date, the business has primarily focused on a business-to-business (B2B) model, serving schools, large corporations, and local government institutions as its main clients. While this approach provides business stability, it also limits market reach and has yet to fully strengthen the identity of Cilegon’s batik among the wider public. Therefore, a more effective branding strategy that leverages the potential of digital marketing is needed.This community service program aims to enhance the capacity of MSMEs to develop a strong and competitive brand identity, while also expanding their market from B2B to business-to-customer (B2C). The program was conducted through several stages, including problem identification through discussions, the preparation and delivery of digital marketing and website development training and evaluation through participat satisfaction surveys. The evaluation result indicate a very high level of satisfaction with an overall average scrore of 4,74. Through this program, Rinara Batik is expected to expand its market reach and strengthen the position of Cilegon’s batik.Abstrak: UMKM Rinara Batik merupakan salah satu pelaku usaha batik khas Kota Cilegon yang selama ini berfokus pada model bisnis business to business (B2B) dengan pelanggan utama sekolah, perusahaan besar, dan pemerintah daerah. Meskipun memberikan stabilitas usaha, pola ini membatasi jangkauan pasar dan belum sepenuhnya memperkuat identitas batik khas Kota Cilegon di kalangan masyarakat luas. Oleh karena itu, diperlukan strategi branding yang lebih efektif dengan memanfaatkan potensi digital marketing. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan kapasitas UMKM dalam mengembangkan identitas merek yang kuat, berdaya saing, serta memperluas pasar dari B2B menuju Business to Customer (B2C). Kegiatan pegabdian ini dilakukan melalui tahapan identifikasi masalah melalui diskusi, penyusunan dan penyampaian materi pelatihan digital marketing dan pembuatah website serta evaluasi kegiatan melalui kepuasan peserta untuk mengukur efetivitas pelatihan. Hasil evaluasi kegiatan menunjukkan tingkat kepuasan yang sangat baik dengan rata-rata skor keseluruhan sebesar 4,74. Dengan kegiatan ini, UMKM Rinara Batik diharapkan mampu memperluas jangkauan pasar, meningkatkan penjualan, sekaligus memperkuat posisi batik khas Kota Cilegon.